The Limbic System and the Soul: Evolution and the Neuroanatomy of Religious Experience - Joseph, R. (Zygon, 2001)
The evolutionary neurological foundations of religious experience are detailed. Human beings have been burying and preparing their dead for the Hereafter for more than 100,000 years. These behaviors and beliefs are related to activation of the amygdala, hippocampus, and temporal lobe, which are responsible for religious, spiritual, and mystical trancelike states, dreaming, astral projection, near-death and out-of-body experiences, and the hallucination of ghosts, demons, angels, and gods. Abraham, Moses, Muhammad, and Jesus Christ, and others who have communed with angels or gods display limbic system hyperactivity, whereas patients report religious hallucinations or out-of-body experiences when limbic structures are stimulated or excessively activated. It is postulated that limbic and temporal lobe structures account for the sexual and violent aspects of religious behavior and also serve as a “transmitter to God,” and that the evolution of these structures made spiritual experience possible.